2018
DOI: 10.5194/acp-18-10497-2018
|View full text |Cite
|
Sign up to set email alerts
|

HTAP2 multi-model estimates of premature human mortality due to intercontinental transport of air pollution and emission sectors

Abstract: Abstract. Ambient air pollution from ozone and fine particulate matter is associated with premature mortality. As emissions from one continent influence air quality over others, changes in emissions can also influence human health on other continents. We estimate global air-pollution-related premature mortality from exposure to PM 2.5 and ozone and the avoided deaths due to 20 % anthropogenic emission reductions from six source regions, North America (NAM), Europe (EUR), South Asia (SAS), East Asia (EAS), Russ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
78
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(79 citation statements)
references
References 63 publications
(127 reference statements)
1
78
0
Order By: Relevance
“…We chose to use the older CRF to enable comparison with previous work for China (Li et al 2018). Finally, the 95% CIs of avoided premature deaths reported here only represent uncertainties in the CRF, and recent studies suggested that it may be exceeded by uncertainties from either simulated air pollution among different models (Liang et al 2018) or climate variability (Saari et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…We chose to use the older CRF to enable comparison with previous work for China (Li et al 2018). Finally, the 95% CIs of avoided premature deaths reported here only represent uncertainties in the CRF, and recent studies suggested that it may be exceeded by uncertainties from either simulated air pollution among different models (Liang et al 2018) or climate variability (Saari et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Increased premature mortality due to ozone exposure is represented with the exposure-response model for ozone-related premature mortality of Turner et al (2016) (equation (1)). The cost function is the annual continental US premature mortality attributable to ozone exposure above a theoretical minimum risk exposure level (TMREL) (Lim et al 2014, Cohen et al 2017, Liang et al 2018, M, defined as…”
Section: Premature Mortalitymentioning
confidence: 99%
“…The value of the TMREL for the annual average MDA8 is set at 28.9 ppb by taking the average of the two LCC values for North America that are estimated based on Turner et al (2016), in which the annual average MDA8 is also used as the exposure metric (Malley et al 2017, Liang et al 2018.…”
Section: Premature Mortalitymentioning
confidence: 99%
See 2 more Smart Citations